Development of a biomimetic nanoparticle platform for apigenin therapy in triple-negative breast cancer - Chenyang Wang; Chenyang Wang; Chenyang Wang; Xiaojing Ren; Xiaojing Ren; Xiaojing Ren; Yanmei Han; Yanmei Han; Yanmei Han; Ding Nan; Ding Nan; Ding Nan; et al. (Frontiers in Oncology)
BackgroundThis study investigates the therapeutic potential and mechanisms of Apigenin (AGN) in treating triple-negative breast cancer (TNBC). Although AGN is recognized for its anti-tumor properties, its specific mechanisms in TNBC remain unclear.MethodsTo identify key genes associated with AGN’s effects on breast cancer, we utilized network pharmacology, conducting Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. We developed a macrophage membrane-coated nanomicelle system (m@peg-AGN) to enhance drug delivery and facilitate immune evasion.ResultsOur analyses identified 21 overlapping genes between AGN and breast cancer, including CDH1, TP53, and CCND1, critical in cancer progression. The m@peg-AGN system demonstrated superior immune evasion and effective tumor targeting, resulting in good tumor suppression without detected toxicity in major organs.ConclusionsThis study demonstrated the targeted tumor genes to TNBC for AGN, then innovatively integrates network pharmacology with biomimetic nanotechnology, developing a novel m@peg-AGN delivery system for TNBC treatment. This system enhanced the AGN’s water solubility and increased the accumulation to the tumor site. This compound has exhibited good anti-tumor effects in vivo, thereby could advance the treatment for TNBC.